Early arterial stasis during resin‐based yttrium‐90 radioembolization: incidence and preliminary outcomes. Issue 4 (19th June 2013) - Piana, Peachy Mae; Bar, Voichita; Doyle, Laura; Anne, Rani; Sato, Takami; Eschelman, David J.; McCann, Jeffrey W.; Gonsalves, Carin F.; Brown, Daniel B.
Abstract Objectives This study was conducted to determine the incidence of early stasis in radioembolization using resin yttrium‐90 (Y‐90) microspheres, to evaluate potential contributing factors, and to review initial imaging outcomes. Methods Patients in whom early stasis occurred were compared with those in whom complete delivery was achieved for tumour type and vascularity, tumour : normal liver ratio (T : N ratio) at technetium‐99m‐macroaggregated albumin (Tc‐99m‐MAA) angiography, previous intra‐arterial therapy, and infusion site (left, right or whole liver). Tumour response was evaluated at 3 months and defined according to whether a partial response and stable disease versus progressive disease were demonstrated. Results A total of 71 patients underwent 128 Y‐90 infusions in which 26 (20.3%) stasis events occurred. Hypervascular and hypovascular tumours had similar rates of stasis (17.4% versus 27.8%; P = NS). The mean ± standard deviation T : N ratio was 3.03 ± 1.54 and 3.66 ± 2.79 in patients with and without stasis, respectively (P = NS). Stasis occurred in 14 of 81 (17.3%) and 12 of 47 (25.5%) infusions following previous intra‐arterial therapy and in therapy‐naïve territories, respectively (P = NS). Early stasis occurred in 15 of 41 (36.6%) left, 10 of 65 (15.4%) right and one of 22 (4.5%) whole liver infusions (P < 0.001). Rates of partial response and stable disease were similar in the stasis (88.3%) and non‐stasis (76.0%) groups (P = NS). Conclusions Early stasis occurred in approximately 20% of infusions with similar incidences in hyper‐ and hypovascular tumours. Whole‐liver therapy reduced the incidence of stasis. Stasis did not appear to affect initial imaging outcomes.